Visitor experience towards signage design and implementation in The Museum / Nur Haziqah Md Salim - Md Salim, Nur Haziqah (2021)
Building signage systems are frequently utilised to comply with safety regulations and building requirements. These are intended to offer visitors with basic information and safety warnings, as well as to aid them in locating themselves during both circulation and evacuation. Despite the fact that signage systems play an essential role in the development of wayfinding systems. There is a deficiency of knowledge on how visitors perceive, comprehend, and use the information provided by emergency signs. As a result, the efficiency of signage systems is difficult to assess and is underrepresented in existing evacuation models. As a consequence, the efficiency of signage systems is difficult to determine and is neglected in consider the legal models. In this research, the issue is address through the unsuitable signage design and implementation which can cause confusion and difficulties towards visitor and staff. Furthermore, the aim of the study is to identify the appropriate signage design and implementation in the museum. The purpose is to investigate the situation based on Malaysia’s museum context of signage design. The objective of this research is to identify the elements of the effective signage design and to investigate the effects of the signage towards user experience and perception. Also, to determine the suitable signage design towards user in the museum. This research is based on data obtained from a survey questionnaire that polled visitor experience towards signage design and implementation in the museum. The data was analysed in order to assess and determine how best to develop and deploy commercial or public display signage for usage in museums. Exploring this issue was necessary in order to provide museums with insight into how to present information in a unique way and produce the most successful wayfinding procedure by allowing visitors to simply move across an exhibit area. This study is intended to enhance understanding of people's interactions with signage, allowing interested parties such as authorities, staff, visitors, and tourists, as well as signage manufacturers and suppliers, and designers, to more effectively and credibly examine the impact of signage systems on pedestrian and emergency movement in the Malaysian Museum.